Hot melt adhesive, preparation method thereof, gummed paper, wound battery cell, battery and electric equipment

By using hot melt adhesive composed of polyolefin, toughening resin and reinforcement resin in the winding battery cell, the problem of pole sheet cracking is solved, the life of the battery cell is improved and the normal operation of the electrolyte is maintained.

CN119193039APending Publication Date: 2024-12-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310753367.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In actual production and application of winding battery cells, excessive stress in some arc-shaped areas causes the pole sheet to crack, affecting the life and normal operation of the battery cells.

Method used

A hot melt adhesive including polyolefin, toughening resin and reinforcement resin is used. The solubility parameter of polyolefin is 15cal1/2/cm3/2-19cal1/2/cm3/2, which is used in the winding battery cell, heat The melt adhesive has low dissolution rate in the electrolyte and has good electrolyte resistance, which serves as a buffering function and reduces the occurrence of pole cracking.

Benefits of technology

It effectively reduces the cracking problem of electrode sheets, improves the life of the battery cell, and ensures the normal operation of the battery cell. The hot melt adhesive does not increase the viscosity in the electrolyte, and maintains the transmission efficiency of active ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193039A_ABST
    Figure CN119193039A_ABST
Patent Text Reader

Abstract

The invention discloses a hot melt adhesive and a preparation method thereof, adhesive paper, a winding cell, a battery and electric equipment, the hot melt adhesive comprises polyolefin, toughening resin and reinforced resin, and the solubility parameter of the polyolefin is 15 cal1 / 2 / cm < 3 > / 2-19 cal1 / 2 / cm < 3 > / 2. When the hot melt adhesive is used for winding a battery cell, the cracking problem of a pole piece can be reduced, and the normal operation of the battery cell is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to hot melt adhesive and a preparation method thereof, adhesive tape, wound battery cells, batteries and electrical equipment. Background Art

[0002] Secondary batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but are also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as in military equipment, aerospace and other fields.

[0003] Wound cells are a widely used type of secondary battery cell. They are made by rolling together the positive electrode sheet, the negative electrode sheet and the isolation film. Therefore, there are arc-shaped areas in the wound cells. In actual production and application, some of the arc-shaped areas will be subjected to excessive force, resulting in cracking of the electrode sheets. Summary of the Invention

[0004] In view of the technical problems existing in the background technology, the present application provides a hot melt adhesive that can reduce the problem of cracking of the electrode.

[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a hot melt adhesive, comprising polyolefin, toughening resin and reinforcing resin, wherein the solubility parameter of the polyolefin is 15cal 1 / 2 / cm 3 / 2 -19cal 1 / 2 / cm 3 / 2 .

[0006] The present application includes at least the following beneficial effects: the hot melt adhesive composed of the present application, when used in winding battery cells, can reduce the problem of cracking of the electrode sheets and will not affect the normal operation of the battery cells.

[0007] In some embodiments of the present application, the dissolution rate of the hot melt adhesive in the organic solvent is less than or equal to 10%, and can be optionally 1%-6%. This can improve the electrolyte resistance of the hot melt adhesive, play a good buffering role, and reduce electrode cracking.

[0008] In some embodiments of the present application, the hot melt adhesive comprises 5-50 parts by weight of polyolefin, 10-40 parts by weight of toughening resin, and 10-40 parts by weight of reinforcing resin. Alternatively, the hot melt adhesive comprises 20-30 parts by weight of polyolefin, 15-25 parts by weight of toughening resin, and 20-30 parts by weight of reinforcing resin. Thus, the hot melt adhesive of the above composition can act as a buffer, significantly improving the problem of electrode cracking.

[0009] In some embodiments of the present application, the solubility parameter of the polyolefin is 15 cal 1 / 2 / cm 3 / 2 -18cal 1 / 2 / cm 3 / 2 , optional 16cal 1 / 2 / cm 3 / 2 -17cal 1 / 2 / cm 3 / 2 This can improve the electrolyte resistance of the hot melt adhesive, play a good buffering role, and reduce the cracking of the electrode.

[0010] In some embodiments of the present application, the weight average molecular weight of the polyolefin is 20,000-100,000, and can be 30,000-50,000. This can improve the electrolyte resistance of the hot melt adhesive, play a good buffering role, and reduce electrode cracking.

[0011] In some embodiments of the present application, the melting point of the polyolefin is 130° C.-150° C., and may be 140° C.-150° C. Thus, the polyolefin can have a certain flexibility, thereby allowing the hot melt adhesive to swell in the electrolyte.

[0012] In some embodiments of the present application, the crystallinity of the polyolefin is 40%-60%, optionally 40%-50%. Within the above crystallinity range, the electrolyte resistance of the hot melt adhesive can be improved, which plays a good buffering role and reduces electrode cracking.

[0013] In some embodiments of the present application, the polyolefin comprises at least one of an amorphous α-olefin copolymer, a polyolefin elastomer, and a polypropylene copolymer. Specifically, the polyolefin comprises at least one of polypropylene, polyethylene, and polystyrene. These polyolefins have strong electrolyte resistance, can improve the electrolyte resistance of the hot melt adhesive, provide a good buffering effect, and reduce electrode cracking.

[0014] In some embodiments of the present application, the toughening resin has a weight-average molecular weight of 10,000-100,000, optionally 30,000-60,000. The toughening resin within this weight-average molecular weight range allows the hot melt adhesive to swell after being immersed in the electrolyte, allowing active ions to freely shuttle between the hot melt adhesive molecular chains without affecting the operation of the battery cell. Furthermore, the toughness of the hot melt adhesive is increased, providing a good buffering effect and reducing electrode cracking.

[0015] In some embodiments of the present application, the toughening resin has a degree of branching of 100-500, optionally 100-200. When the degree of branching of the toughening resin is within this range, the hot melt adhesive can swell after being immersed in the electrolyte, and active ions can freely shuttle and transport between the hot melt adhesive molecular chains without affecting the operation of the battery cell. Furthermore, the toughness of the hot melt adhesive can be improved, providing a good buffering effect and reducing electrode cracking.

[0016] In some embodiments of the present application, the toughening resin includes at least one of butyl acrylate, poly(2-ethylhexyl acrylate), amino-terminated liquid nitrile rubber, and vinyl-terminated liquid nitrile rubber. A hot melt adhesive containing such a toughening resin does not affect the operation of the battery cell, but rather improves the toughness of the hot melt adhesive, providing a good buffering effect and reducing electrode cracking.

[0017] In some embodiments of the present application, the weight-average molecular weight of the reinforcing resin is 30,000-100,000, and optionally 50,000-80,000. Within this weight-average molecular weight range, the reinforcing resin does not affect the operation of the battery cell, and can improve the strength of the hot melt adhesive and the wettability of the electrolyte, providing a good buffering effect and reducing electrode cracking without affecting the normal operation of the battery cell.

[0018] In some embodiments of the present application, the degree of branching of the reinforcing resin is 100-500, and can be optionally 100-200. Within the above range, the degree of branching of the reinforcing resin will not affect the operation of the battery cell, and can increase the strength of the hot melt adhesive, play a good buffering role, and reduce cracking of the electrode.

[0019] In some embodiments of the present application, the reinforcing resin includes at least one of butyl rubber and styrene-butadiene rubber. The hot melt adhesive containing the reinforcing resin does not affect the operation of the battery cell, and can increase the strength of the hot melt adhesive, enhance the buffering effect, and reduce cracking of the electrode.

[0020] In some embodiments of the present application, the hot melt adhesive further comprises 5 to 30 parts by weight of a tackifying resin, and optionally 10 to 20 parts by weight of a tackifying resin, thereby increasing the viscosity of the hot melt adhesive and improving the bonding strength between the hot melt adhesive and the electrode.

[0021] In some embodiments of the present application, the weight average molecular weight of the tackifying resin is 1000-10000, and can be optionally 3000-5000. Within the weight average molecular weight range of the tackifying resin, the viscosity of the hot melt adhesive can be increased, and the bonding force between the hot melt adhesive and the electrode can be improved.

[0022] In some embodiments of the present application, the melting point of the tackifying resin is 60° C.-90° C., and can be optionally 75° C.-85° C. Within the melting point range of the tackifying resin, the flexibility of the tackifying resin can be increased, thereby improving the adhesiveness of the hot melt adhesive.

[0023] In some embodiments of the present application, the viscosity of the tackifying resin at 100° C. is 200 mPa·S-1500 mPa·S, optionally 500 mPa·S-1000 mPa·S. The viscosity of the tackifying resin at 100° C. is within the above range, which can improve the bonding strength between the hot melt adhesive and the electrode.

[0024] In some embodiments of the present application, the tackifying resin includes at least one of a C5 / C9 copolymer petroleum resin, a hydrogenated petroleum resin, and a terpene resin. Thus, the tackifying resin can increase the viscosity of the hot melt adhesive and improve the bonding strength between the hot melt adhesive and the electrode.

[0025] In some embodiments of the present application, the hot melt adhesive further comprises 0.1 to 1 parts by weight of an additive. Optionally, the hot melt adhesive further comprises 0.1 to 0.5 parts by weight of an additive.

[0026] In some embodiments of the present application, the additive includes at least one of N-phenyl-β-naphthylamine, 2,6-di-tert-butyl-p-cresol, 3-methyl-6-tert-butylphenol, and pentaerythritol tetrakis(3-laurylthiopropionate), thereby improving the antioxidant properties of the hot melt adhesive.

[0027] The second aspect of the present application provides a method for preparing a hot melt adhesive, comprising: mixing a polyolefin, a toughening resin and a reinforcing resin to obtain a hot melt adhesive, wherein the solubility parameter of the polyolefin is 15 cal 1 / 2 / cm 3 / 2 -19cal 1 / 2 / cm 3 / 2 .

[0028] Therefore, the hot melt adhesive prepared by this method has good electrolyte resistance and good adhesion to the electrode. When the hot melt adhesive is used on the electrode, the hot melt adhesive plays a buffering role when the electrode is subjected to pressure, which can greatly improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.

[0029] The third aspect of the present application provides an adhesive tape comprising a substrate and an adhesive layer provided on at least one side of the substrate, wherein the adhesive layer comprises the hot melt adhesive described in the first aspect of the present application or the hot melt adhesive prepared by the method described in the second aspect of the present application.

[0030] In some embodiments of the present application, the adhesive tape satisfies at least one of the following conditions:

[0031] The thickness ratio of the adhesive layer to the substrate is (1-4):10, and can be optionally (1-2):10;

[0032] The thickness of the adhesive tape is 2 μm-8 μm, and can be optionally 2 μm-4 μm.

[0033] The adhesive tape meets at least one of the above conditions. When used on the electrode, the hot melt adhesive plays a buffering role when the electrode is subjected to pressure, which can greatly improve the problem of electrode cracking, increase the life of the battery cell, and will not affect the normal operation of the battery cell.

[0034] The fourth aspect of the present application proposes a wound battery cell, comprising a positive electrode sheet, an isolation membrane and a negative electrode sheet stacked and wound in sequence, and the adhesive tape described in the third aspect of the present application is provided between the positive electrode sheet and the isolation membrane and / or between the negative electrode sheet and the isolation membrane.

[0035] Adhesive paper is arranged between the positive electrode plate and the isolation membrane and / or between the negative electrode plate and the isolation membrane. The hot melt adhesive has good electrolyte resistance and good bonding performance with the electrode plate. The hot melt adhesive plays a buffering role when the electrode plate is subjected to pressure, which can greatly improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.

[0036] In some embodiments of the present application, the positive electrode plate includes alternating flat sections and curved sections, with the adhesive tape applied to at least one side of the curved section. As a result, the curved section has an arc-shaped area that is subject to high forces. Applying adhesive tape to at least one side of the curved section can significantly reduce the problem of plate cracking, extending the lifespan of the battery cell without affecting normal operation of the battery cell.

[0037] In some embodiments of the present application, the adhesive tape is applied on at least one side of the bent section near the center of the wound cell. Therefore, the bent section near the center of the wound cell is subject to high stress and is prone to cracking. Applying adhesive tape on at least one side of the bent section near the center of the wound cell can alleviate the problem of electrode cracking and increase the lifespan of the cell without affecting the cell's energy density due to excessive adhesive tape application.

[0038] The fifth aspect of the present application provides a battery comprising the wound battery cell according to the fourth aspect of the present application, thereby providing the battery with a longer lifespan.

[0039] The sixth aspect of the present application provides an electrical device, comprising the battery according to the fifth aspect of the present application, so that the electrical device has a longer lifespan.

[0040] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become obvious from the description below, or will be learned through practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiment below. The accompanying drawings are for illustration purposes only and are not to be considered as limiting the present application. The same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0042] Figure 1 This is a schematic structural diagram of a wound battery cell from one perspective according to one embodiment of the present application;

[0043] Figure 2yes Figure 1 A schematic diagram of the partial structure of the middle positive electrode plate in the unfolded state;

[0044] Figure 3 1 is a schematic structural diagram of a battery according to an embodiment of the present application;

[0045] Figure 4 is a schematic structural diagram of a battery module according to an embodiment of the present application;

[0046] Figure 5 is a schematic structural diagram of a battery pack according to one embodiment of the present application;

[0047] Figure 6 yes Figure 5 Exploded view of

[0048] Figure 7 It is a schematic diagram of an embodiment of an electric device using a battery as a power source.

[0049] Description of reference numerals:

[0050] 10: wound battery cell; 101: negative electrode sheet; 102: positive electrode sheet; 103: separator; 102-1: bent section of the positive electrode sheet; 101-1: bent section of the negative electrode sheet; 106: adhesive tape; 102-2: flat section of the positive electrode sheet; 1: secondary battery; 2: battery module; 3: battery pack; 4: upper case; 5: lower case. DETAILED DESCRIPTION

[0051] The following embodiments of the technical solution of the present application are described in detail. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only used as examples and are not intended to limit the scope of protection of the present application.

[0052] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0053] For the sake of clarity, only some numerical ranges are specifically disclosed herein. However, any lower limit may be combined with any upper limit to form an unspecified range; and any lower limit may be combined with other lower limits to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each individually disclosed point or single value may itself serve as a lower limit or upper limit and be combined with any other point or single value, or with other lower limits or upper limits, to form an unspecified range.

[0054] In the description of the embodiments of this application, the term "and / or" is simply a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this document generally indicates that the associated objects are in an "or" relationship.

[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0056] Currently, market developments indicate that secondary batteries are becoming increasingly widely used. They are not only used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, but are also widely used in electric vehicles like electric bicycles, electric motorcycles, and electric vehicles, as well as in military equipment and aerospace. As the application of secondary batteries continues to expand, market demand is also growing.

[0057] Wound cells are a widely used type of secondary battery cell. They are made by rolling together positive and negative electrode sheets and separators. Therefore, wound cells have curved areas. In actual production and application, some areas may be subjected to excessive force, resulting in cracking of the electrode sheets. This problem will cause lithium deposition during the cycle of the cell. Over time, the deposited lithium slowly turns into lithium dendrites, which pierce the separator and cause a short circuit inside the cell.

[0058] To reduce the stress on the electrode, hot melt adhesive can be placed on one side of the electrode to act as a buffer. However, due to the presence of a large amount of organic solvents in the electrolyte, existing hot melt adhesives easily dissolve into the electrolyte when used on the electrode. On the one hand, the hot melt adhesive cannot act as a buffer. On the other hand, after the hot melt adhesive dissolves in the electrolyte, it increases the viscosity of the electrolyte, reduces the ionic conductivity of the electrolyte, and thus affects the transmission of active ions in the electrolyte. In addition, after the hot melt adhesive dissolves in the electrolyte, it will enter the positive and negative electrode sheets during the charge and discharge cycle of the wound battery cell, deteriorating the electrodes.

[0059] When the hot melt adhesive composition of this application is used on the electrode sheets of wound battery cells, the hot melt adhesive acts as a buffer when the electrode sheets are subjected to pressure, effectively improving the problem of electrode sheet cracking and extending the life of the battery cell. Furthermore, the hot melt adhesive composition has a low dissolution rate in the electrolyte and good electrolyte resistance. After being immersed in the electrolyte, it swells, increasing the spacing between the hot melt adhesive molecular chains, allowing active ions to freely shuttle and transmit between the hot melt adhesive molecular chains. In other words, the hot melt adhesive will not affect the normal operation of the wound battery cell, and can act as a buffer to improve electrode sheet cracking.

[0060] The hot melt adhesive disclosed in the embodiments of the present application can be used for batteries, and the batteries disclosed in the embodiments of the present application can be used in electrical devices that use batteries as power sources or various energy storage systems that use batteries as energy storage elements. Electrical devices may include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.

[0061] The first aspect of the present application provides a hot melt adhesive, comprising polyolefin, toughening resin and reinforcing resin, wherein the solubility parameter of the polyolefin is 15 cal 1 / 2 / cm 3 / 2 -19cal 1 / 2 / cm 3 / 2 .

[0062] The present application includes at least the following beneficial effects: when the hot melt adhesive proposed in the present application is used on the electrode, the hot melt adhesive plays a buffering role when the electrode is subjected to pressure, which can well improve the problem of electrode cracking and increase the life of the battery cell; in addition, the hot melt adhesive has a low dissolution rate in the electrolyte, which makes the hot melt adhesive have good electrolyte resistance, and the hot melt adhesive is not easy to increase the viscosity of the electrolyte in the electrolyte, which reduces the deterioration of the conductivity of the electrolyte caused by the hot melt adhesive, and at the same time reduces the deterioration of the electrode caused by the hot melt adhesive dissolved in the electrolyte; the hot melt adhesive swells after being soaked in the electrolyte, which increases the spacing between the hot melt adhesive molecular chains, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains. In summary, the hot melt adhesive proposed in the present application, the three components work together, so that the hot melt adhesive has a low dissolution rate in the electrolyte and can swell in the electrolyte. When the hot melt adhesive is used to wind the battery cell, it can reduce the problem of electrode cracking and will not affect the normal operation of the battery cell.

[0063] The solubility parameter is a parameter that characterizes the polymer-solvent interaction. When the solubility parameters of two materials are similar, they can be blended with each other and have good compatibility. In the examples of this application, the solubility parameter of the polyolefin is determined as follows:

[0064] (1) Selection of solvent and precipitant: First determine the solubility parameter δ of polyolefin p Range: Take a small amount of sample and conduct solubility test in solvents with different solubility parameters (δ). If it is insoluble or dissolves slowly at room temperature, heat the polyolefin and solvent together and cool the hot solution to room temperature. If no precipitate is formed, it is considered soluble. Select the appropriate solvent and precipitant from these.

[0065] (2) Prepare a polymer solution based on the selected solvent: Weigh about 0.2 g of a polyolefin sample and dissolve it in 25 ml of a solvent (using chloroform as the solvent). Use a pipette to draw 5 ml (or 10 ml) of the solution into a test tube. First, titrate the polymer solution with n-pentane until a precipitate appears. Shake the test tube to dissolve the precipitate. Continue to add n-pentane until the precipitate becomes difficult to dissolve. Titrate until the precipitate is just no longer soluble, and record the volume of n-pentane used. Then titrate with methanol, following the same procedure as for n-pentane, and record the volume of methanol used.

[0066] (3) Weigh 0.1 g and 0.05 g of the above polyolefin sample respectively, dissolve them in 25 ml of solvent, and titrate them in the same manner as above.

[0067] Calculate the solubility parameter δ of the mixture according to formula (1) mh and δ ml

[0068]

[0069] Where: and represent the volumes of n-pentane and methanol, respectively; δ1 and δ2 represent the solubility parameters of n-pentane and methanol, respectively.

[0070] The solubility parameter of polyolefins was calculated by formula (2).

[0071] δ p =1 / 2(δ mh +δ ml ) (2)

[0072] In some embodiments of the present application, the solubility parameter of the polyolefin may be 15 cal 1 / 2 / cm 3 / 2 -18.8cal 1 / 2 / cm 3 / 2 , 15.2cal 1 / 2 / cm 3 / 2 -18.5cal 1 / 2 / cm 3 / 2 , 15.5cal 1 / 2 / cm 3 / 2 -18cal 1 / 2 / cm3 / 2 , 15.8cal 1 / 2 / cm 3 / 2 -17.8cal 1 / 2 / cm 3 / 2 , 16cal 1 / 2 / cm 3 / 2 -18.5cal 1 / 2 / cm 3 / 2 , 16.5cal 1 / 2 / cm 3 / 2 -18cal 1 / 2 / cm 3 / 2 , 17cal 1 / 2 / cm 3 / 2 -17.5cal 1 / 2 / cm 3 / 2 The solubility parameter of the polyolefin is within the range of 15 cal, which is different from the solubility parameter of the electrolyte. This makes the hot melt adhesive have good electrolyte resistance. The hot melt adhesive is not easy to increase the viscosity of the electrolyte in the electrolyte, which reduces the deterioration of the conductivity of the electrolyte by the hot melt adhesive. At the same time, it reduces the deterioration of the electrode by the hot melt adhesive dissolving in the electrolyte. In other embodiments of the present application, the solubility parameter of the polyolefin is 15 cal 1 / 2 / cm 3 / 2 -18cal 1 / 2 / cm 3 / 2 , for example 16cal 1 / 2 / cm 3 / 2 -17cal 1 / 2 / cm 3 / 2 .

[0073] In some embodiments of the present application, the dissolution rate of the hot melt adhesive in an organic solvent is 1%-10%. Specifically, the dissolution rate refers to the ratio of the mass of the hot melt adhesive dissolved in the organic solvent to the initial mass of the hot melt adhesive. The method for determining the dissolution rate of the hot melt adhesive in an organic solvent is as follows:

[0074] 1) Weigh a certain mass of hot melt adhesive, record it as M1

[0075] 2) immersing in an electrolyte at 70°C for 5 hours, wherein the electrolyte comprises ethylene carbonate (EC), ethyl methyl carbonate (EMC), and an electrolyte salt LiPF6, wherein the mass ratio of EC to EMC in the electrolyte is 30:70 and the molar concentration of the electrolyte salt is 1.0 mol / L;

[0076] 3) Take out the hot melt adhesive and wipe the surface dry with dust-free paper;

[0077] 4) Immerse the hot melt adhesive in dimethyl carbonate (DMC) at 70°C for 24 hours;

[0078] 5) Take out the hot melt adhesive and wipe the surface dry with dust-free paper;

[0079] 6) Place the hot melt adhesive in an oven at 90°C and dry for 24 hours;

[0080] 7) Take out the membrane and weigh it, record it as M2

[0081] 8) Calculate the dissolution rate = (M1-M2) x 100% / M1.

[0082] Therefore, the dissolution rate of the hot melt adhesive in the organic solvent is less than or equal to 10%. For example, the dissolution rate of the hot melt adhesive in the organic solvent can be 0.2%-10%, 1%-10%, 2%-9%, 3%-7%, 4%-6%, etc. Specifically, the dissolution rate of the hot melt adhesive in the organic solvent is within the above range, so that the hot melt adhesive has good electrolyte resistance, the hot melt adhesive is not easy to increase the viscosity of the electrolyte in the electrolyte, and the deterioration of the electrolyte conductivity caused by the hot melt adhesive is reduced. At the same time, the deterioration of the electrode caused by the hot melt adhesive dissolving in the electrolyte is reduced. Without affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the electrode. In other embodiments of the present application, the dissolution rate of the hot melt adhesive in the organic solvent is 1%-6%.

[0083] In some embodiments of the present application, the organic solvent includes an organic solvent in the electrolyte. As an example, the organic solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0084] In some embodiments of the present application, the hot melt adhesive includes 5-50 parts by weight of polyolefin. For example, the hot melt adhesive includes 5-45 parts by weight of polyolefin, 10-40 parts by weight of polyolefin, 15-35 parts by weight of polyolefin, 20-30 parts by weight of polyolefin, etc. Therefore, the use of the polyolefin content in this application can improve the electrolyte resistance of the hot melt adhesive, play a good buffering role without affecting the normal operation of the battery cell, and reduce the cracking of the electrode. In other embodiments of the present application, the hot melt adhesive includes 20-30 parts by weight of polyolefin.

[0085] In some embodiments of the present application, the weight-average molecular weight of the polyolefin is 20,000-100,000. For example, the weight-average molecular weight of the polyolefin can be 20,000-90,000, 30,000-80,000, 40,000-70,000, 50,000-60,000, etc. Therefore, using a polyolefin that meets the weight-average molecular weight of this application can improve the hot melt adhesive's electrolyte resistance and adhesion to the electrode, reduce the risk of hot melt adhesive shedding during battery cycling, provide a good buffering effect, and reduce electrode cracking. In other embodiments of the present application, the weight-average molecular weight of the polyolefin is 30,000-50,000.

[0086] The weight average molecular weight of the polyolefin can be measured by methods commonly used in the art, such as light scattering, ultracentrifugal sedimentation velocity, and gel chromatography.

[0087] The method for determining the weight average molecular weight of other substances below is the same as above.

[0088] In some embodiments of the present application, the melting point of the polyolefin is 130°C-150°C. For example, the melting point of the polyolefin can be 133°C-147°C, 136°C-144°C, 139°C-141°C, etc. Therefore, the use of polyolefins with the melting point of the present application can improve the flexibility of the hot melt adhesive, thereby allowing the hot melt adhesive to swell in the electrolyte, and play a good buffering role without affecting the normal operation of the battery cell, thereby reducing the cracking of the electrode. In other embodiments of the present application, the melting point of the polyolefin is 140°C-150°C.

[0089] In this application, the melting point of the polyolefin described herein can be measured using methods commonly used in the art, such as a microscopic melting point tester. A polymer sample is placed at the center of a hot plate surface, covered with insulating glass to form an insulated, enclosed chamber. The hot plate is heated at a constant rate. When the temperature reaches the polymer melting point, a significant increase in transparency in a portion of the polymer sample, which gradually spreads to the entire sample, can be clearly observed under a microscope. The hot plate temperature is displayed using a mercury-in-glass thermometer. The instant the sample melts, the temperature is read on the thermometer, which represents the melting point of the sample.

[0090] The melting points of other substances are determined using the same method as above.

[0091] In some embodiments of the present application, the polyolefin has a crystallinity of 40%-60%. For example, the crystallinity of the polyolefin can be 40%-58%, 43%-55%, 45%-52%, 47%-50%, etc. Within this crystallinity range, the hot melt adhesive's electrolyte resistance can be improved, providing a good buffering effect and reducing electrode cracking without affecting the normal operation of the battery cell. In other embodiments of the present application, the polyolefin has a crystallinity of 40%-50%.

[0092] In this application, the test method for "crystallinity of polyolefin" can be measured by methods commonly used in the art, for example, using DSC measurement: using a Mettler Toledo 821e DSC test, about 10 mg of sample is heated to 180°C at 10°C / min, kept at this temperature for 2 minutes, and then cooled to 80°C at 10°C / min. The crystallinity obtained by DSC can be calculated using the following formula:

[0093] X cd =ΔH m / ΔH m 0 ,

[0094] Where ΔH m and ΔH m 0 are the melting heat of the sample and the melting heat of the fully crystallized sample, respectively.

[0095] In some embodiments of the present application, the polyolefin comprises at least one of an amorphous α-olefin copolymer, a polyolefin elastomer, and a polypropylene copolymer. Specifically, the polyolefin comprises at least one of polypropylene, polyethylene, and polystyrene. These polyolefins have strong electrolyte resistance, which can improve the electrolyte resistance of the hot melt adhesive. This provides a good buffering effect and reduces electrode cracking without affecting the normal operation of the battery cell.

[0096] In some embodiments of the present application, the polyolefin also includes modified polyolefin formed by physical or chemical modification.

[0097] In some embodiments of the present application, the hot melt adhesive includes 10-40 parts by weight of a toughening resin, for example, 10-35 parts by weight of a toughening resin, 15-30 parts by weight of a toughening resin, 20-25 parts by weight of a toughening resin, etc. Thus, by using the toughening resin in the content of the present application, the hot melt adhesive can swell after being soaked in the electrolyte, the spacing between the molecular chains increases, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains, which will not affect the operation of the battery cell, and can improve the toughness of the hot melt adhesive. Without affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the electrode. In other embodiments of the present application, the hot melt adhesive includes 15-25 parts by weight of a toughening resin.

[0098] In some embodiments of the present application, the weight-average molecular weight of the toughening resin is 10,000-100,000. For example, the weight-average molecular weight of the toughening resin can be 20,000-90,000, 30,000-80,000, 40,000-70,000, 50,000-60,000, etc. Thus, using the toughening resin with the weight-average molecular weight of the present application allows the hot melt adhesive to swell after being immersed in the electrolyte, increasing the spacing between the molecular chains. Active ions can freely shuttle between the hot melt adhesive molecular chains, providing a good buffering effect and reducing electrode cracking without affecting the normal operation of the battery cell. In other embodiments of the present application, the weight-average molecular weight of the toughening resin is 30,000-60,000.

[0099] In some embodiments of the present application, the degree of branching of the toughening resin is 100-500. For example, the degree of branching of the toughening resin can be 100-450, 150-400, 200-350, 250-300, etc. The degree of branching of the toughening resin within the above range allows the hot melt adhesive to swell after being immersed in the electrolyte, increasing the spacing between the molecular chains. Active ions can freely shuttle between the gaps between the hot melt adhesive molecular chains, providing a good buffering effect and reducing cracking of the electrode without affecting the normal operation of the battery cell. In other embodiments of the present application, the degree of branching of the toughening resin is 100-200.

[0100] The degree of branching refers to the number of branching points per unit volume or the average relative molecular weight between branching points. The degree of branching can be determined using gel permeation chromatography (GPC). Specifically, the polymer sample to be measured is first solvated, and then the solution is filtered through a filter to remove monomer molecules. A surfactant can also be added in this step to reduce the ability of the molecules to adhere to the column. The filtered solution is then placed in a GPC instrument. The pump in the instrument will gradually bring the solution into the column according to the dilution rate based on a pre-set flow gradient. The molecules are brought into the filter layer in the column from the inside out according to their molecular size, and the molecules are separated. Finally, the degree of branching value in the polymer is calculated based on the molecular weight brought out.

[0101] The method for determining the degree of branching of other substances hereinafter is the same as above.

[0102] In some embodiments of the present application, the toughening resin includes at least one of polybutyl acrylate, polyisooctyl acrylate, amino-terminated liquid nitrile rubber, and vinyl-terminated liquid nitrile rubber. The hot melt adhesive containing this toughening resin swells when immersed in electrolyte, increasing the spacing between molecular chains. Active ions can freely shuttle between the hot melt adhesive molecular chains without affecting the operation of the battery cell. Furthermore, the toughness of the hot melt adhesive is increased, providing a good buffering effect and reducing electrode cracking.

[0103] It can be understood that amino-terminated liquid nitrile rubber refers to a liquid nitrile polymer containing an amino group (-NH2) at the chain end, abbreviated as ATBN, which can have a good toughening effect; vinyl-terminated liquid nitrile rubber refers to a liquid nitrile polymer containing a vinyl group at the chain end.

[0104] In some embodiments of the present application, the hot melt adhesive includes 10-40 parts by weight of a reinforcing resin, for example, 10-35 parts by weight of a reinforcing resin, 15-30 parts by weight of a reinforcing resin, 20-25 parts by weight of a reinforcing resin, etc. Therefore, the reinforcing resin of the content of the present application can swell after being soaked in the electrolyte, the spacing between the molecular chains increases, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains without affecting the operation of the battery cell. In addition, the reinforcing resin can increase the strength of the hot melt adhesive, making the buffering effect on the electrode pressure obvious, and can also improve the wetting performance of the electrolyte on the hot melt adhesive, playing a good buffering role without affecting the normal operation of the battery cell, and reducing the cracking of the electrode. In other embodiments of the present application, the hot melt adhesive includes 20-30 parts by weight of a reinforcing resin.

[0105] In some embodiments of the present application, the weight-average molecular weight of the reinforcing resin is 30,000-100,000. For example, the weight-average molecular weight of the reinforcing resin can be 30,000-95,000, 35,000-90,000, 40,000-85,000, 45,000-80,000, 50,000-75,000, 55,000-70,000, 60,000-65,000, etc. Therefore, the reinforcing resin with the weight-average molecular weight of the present application can swell after being soaked in the electrolyte, and the spacing between the molecular chains increases. Active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains without affecting the operation of the battery cell. It can also increase the strength of the hot melt adhesive and enhance the wettability of the electrolyte. Without affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the electrode. In other embodiments of the present application, the weight-average molecular weight of the reinforcing resin is 50,000-80,000.

[0106] In some embodiments of the present application, the degree of branching of the reinforcing resin is 100-500. For example, the degree of branching of the reinforcing resin can be 100-450, 150-400, 200-350, 250-300, etc. Within the above range, the reinforcing resin can swell after being immersed in the electrolyte, the spacing between the molecular chains increases, and the active ions can freely shuttle and transmit between the gaps between the hot melt adhesive molecular chains without affecting the operation of the battery cell. It can also increase the strength of the hot melt adhesive, improve the wettability of the electrolyte, play a good buffering role, and reduce cracking of the electrode. In other embodiments of the present application, the degree of branching of the reinforcing resin is 100-200.

[0107] In some embodiments of the present application, the reinforcing resin includes at least one of butyl rubber and styrene-butadiene rubber. The hot melt adhesive containing this reinforcing resin does not affect the operation of the battery cell, but rather increases the strength of the hot melt adhesive, enhances its buffering effect, improves electrolyte wettability, and provides a good buffering effect, thereby reducing electrode cracking.

[0108] In some embodiments of the present application, the toughening resin and the reinforcing resin serve as swelling components and can swell in the electrolyte. The active ions can freely shuttle and transport in the gaps between the hot melt adhesive molecular chains without affecting the operation of the battery cell. In addition, the toughness and strength of the hot melt adhesive can be improved, thereby playing a good buffering role and reducing the cracking of the electrode.

[0109] In some embodiments of the present application, the hot melt adhesive further comprises 5-30 parts by weight of a tackifying resin. For example, the hot melt adhesive further comprises 5-25 parts by weight of a tackifying resin, 10-20 parts by weight of a tackifying resin, 15-20 parts by weight of a tackifying resin, etc. Specifically, the use of the tackifying resin in the amount described in this application can increase the viscosity of the hot melt adhesive, reduce the probability of the hot melt adhesive falling off during battery cycling, play a good buffering role, and reduce cracking of the electrode. In other embodiments of the present application, the reinforcing resin further comprises 10-20 parts by weight of a tackifying resin.

[0110] In some embodiments of the present application, the weight average molecular weight of the tackifying resin is 1000-10000. For example, the weight average molecular weight of the tackifying resin can be 1000-9000, 2000-8000, 3000-7000, 4000-6000, etc. Specifically, within the weight average molecular weight range of the above tackifying resin, the viscosity of the hot melt adhesive can be increased, and the probability of the hot melt adhesive falling off during the battery cycle can be reduced. Without affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the electrode. In other embodiments of the present application, the weight average molecular weight of the tackifying resin is 3000-5000.

[0111] In some embodiments of the present application, the melting point of the tackifying resin is 60°C-90°C. For example, the melting point of the tackifying resin can be 60°C-85°C, 65°C-80°C, 70°C-75°C, etc. Within the melting point range of the above tackifying resin, the flexibility of the tackifying resin can be improved, the adhesion of the hot melt adhesive can be improved, and the probability of the hot melt adhesive falling off during the battery cycle can be reduced. Without affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the electrode. In other embodiments of the present application, the melting point of the tackifying resin is 75°C-85°C.

[0112] In some embodiments of the present application, the viscosity of the tackifying resin at 100°C is 200mPa·S-1500mPa·S. For example, the viscosity of the tackifying resin at 100°C can be 200mPa·S-1300mPa·S, 300mPa·S-1200mPa·S, 400mPa·S-1100mPa·S, 500mPa·S-1000mPa·S, 600mPa·S-900mPa·S, 700mPa·S-800mPa·S, etc. The viscosity of the tackifying resin at 100°C is within the above range, which can improve the bonding force between the hot melt adhesive and the electrode, reduce the probability of the hot melt adhesive falling off during the battery cycle, and play a good buffering role without affecting the normal operation of the battery cell, thereby reducing the cracking of the electrode. In other embodiments of the present application, the viscosity of the tackifying resin at 100°C is 500mPa·S-1000mPa·S.

[0113] In the examples of the present application, the viscosity of the tackifying resin at 100° C. is tested using a viscometer. The specific method may refer to GBT 1548-2004.

[0114] In some embodiments of the present application, the tackifying resin includes at least one of a C5 / C9 copolymer petroleum resin, a hydrogenated petroleum resin, and a terpene resin. Thus, the tackifying resin can increase the viscosity of the hot melt adhesive, improve the adhesion between the hot melt adhesive and the electrode, and reduce the probability of the hot melt adhesive falling off during battery cycling. Without affecting the normal operation of the battery cell, it provides a good buffering effect and reduces electrode cracking.

[0115] It can be understood that C5 petroleum resin is a thermoplastic resin produced by polymerizing the C5 fraction, a byproduct of ethylene cracking, in the presence of a catalyst, or copolymerizing it with anhydrides, phenols, or aromatic hydrocarbons. C9 petroleum resin is a thermoplastic resin produced by polymerizing the C9 fraction, a byproduct of ethylene cracking, in the presence of a catalyst, or copolymerizing it with anhydrides, phenols, or aromatic hydrocarbons. C5 / C9 copolymerized petroleum resin is a C9 petroleum resin modified by copolymerizing C5 petroleum resin. Its properties as both aliphatic and aromatic resins improve its compatibility with other components of hot melt adhesives.

[0116] In some embodiments of the present application, the hot melt adhesive further comprises 0.1 to 1 parts by weight of an additive, for example, the hot melt adhesive further comprises 0.1 to 0.9 parts by weight of an additive, 0.2 to 0.8 parts by weight of an additive, 0.3 to 0.7 parts by weight of an additive, 0.4 to 0.6 parts by weight of an additive, etc. In other embodiments of the present application, the hot melt adhesive further comprises 0.1 to 0.5 parts by weight of an additive.

[0117] In some embodiments of the present application, the additive includes at least one of N-phenyl-β-naphthylamine, 2,6-di-tert-butyl-p-cresol, 3-methyl-6-tert-butylphenol, and pentaerythritol tetrakis(3-laurylthiopropionate). This can improve the hot melt adhesive's antioxidant properties, extend its lifespan, and provide a good buffering effect, reducing electrode cracking without affecting the normal operation of the battery cell.

[0118] The second aspect of the present application provides a method for preparing a hot melt adhesive, comprising: mixing polyolefin, toughening resin and reinforcing resin to obtain a hot melt adhesive, wherein the solubility parameter of the polyolefin is 15 cal 1 / 2 / cm 3 / 2 -19cal 1 / 2 / cm 3 / 2 .

[0119] Therefore, the hot melt adhesive prepared by this method has good electrolyte resistance and good bonding performance with the electrode. When the hot melt adhesive is used on the electrode, the hot melt adhesive plays a buffering role when the electrode is subjected to pressure, which can greatly improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.

[0120] The third aspect of the present application provides an adhesive tape comprising a substrate and an adhesive layer provided on at least one side of the substrate, wherein the adhesive layer comprises the hot melt adhesive described in the first aspect of the present application or the hot melt adhesive prepared by the method described in the second aspect of the present application.

[0121] In some embodiments, the substrate can be made of the same material as the battery separator. Any known porous separator with electrochemical and mechanical stability can be selected based on actual needs. For example, the substrate can be a single-layer or multi-layer film comprising at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. This ensures excellent electrolyte resistance, allowing active ions to penetrate the pores on the substrate surface, providing some protection for the electrode without reducing the battery's energy density.

[0122] In some specific embodiments, the thickness ratio of the adhesive layer to the substrate is (1-4):10. For example, the thickness ratio of the adhesive layer to the substrate can be (1-3.5):10, (1.5-3):10, (2-3):10, etc. The substrate can provide a certain buffering support for the electrode. When the thickness ratio of the adhesive layer to the substrate is within the above range, the hot melt adhesive can play a good buffering role, enhance the buffering effect, and improve the wettability of the electrolyte. Without affecting the normal operation of the battery cell, it can play a good buffering role and reduce the cracking of the electrode. In other embodiments of the present application, the thickness ratio of the adhesive layer to the substrate is (1-2):10.

[0123] In some embodiments of the present application, the thickness of the adhesive tape is 2 μm-8 μm. For example, the thickness of the adhesive tape can be 2 μm-7 μm, 3 μm-6 μm, 4 μm-5 μm, etc. Within the above range, the thickness of the adhesive tape can effectively exert the buffering effect of the hot melt adhesive, enhance the buffering effect, and improve the wettability of the electrolyte. Without affecting the normal operation of the battery cell, it can play a good buffering role and reduce the cracking of the electrode. In other embodiments of the present application, the thickness of the adhesive tape is 2 μm-4 μm.

[0124] In some embodiments of the present application, the adhesive tape is prepared as follows: hot melt adhesive is applied to a substrate to form an adhesive layer, and a release agent is then applied to the side of the adhesive layer facing away from the substrate. The adhesive layer of the adhesive tape is affixed to at least one side of the positive electrode sheet and / or the negative electrode sheet, contacting the positive electrode sheet and / or the negative electrode sheet.

[0125] In some embodiments of the present application, the release agent preparation method is as follows: cobalt blue powder and phthalocyanine blue are stirred and dispersed in a polyurethane solution, and a solvent is added for dilution while stirring. The solvent can be at least one of toluene, ethyl acetate, and n-hexane. The stirring temperature can be 50°C-70°C, for example, the stirring temperature can be 50°C-65°C, 55°C-60°C, etc. The stirring time can be 30-60 minutes, for example, the stirring time can be 30 minutes-55 minutes, 35 minutes-50 minutes, 40 minutes-45 minutes, etc.

[0126] The fourth aspect of the present application proposes a wound battery cell, comprising a positive electrode sheet, an isolation membrane and a negative electrode sheet stacked and wound in sequence, and the adhesive tape described in the third aspect of the present application is provided between the positive electrode sheet and the isolation membrane and / or between the negative electrode sheet and the isolation membrane.

[0127] In some embodiments of the present application, reference Figure 1 The wound battery cell 10 includes: a positive electrode sheet 102, a separator 103 and a negative electrode sheet 101 stacked and wound in sequence, and the adhesive tape 106 is provided between the positive electrode sheet 102 and the separator 103 and / or between the negative electrode sheet 101 and the separator 103.

[0128] Adhesive paper 106 is arranged between the positive electrode sheet 102 and the isolation membrane 103 and / or between the negative electrode sheet 101 and the isolation membrane 103. The hot melt adhesive of the adhesive paper 106 has good electrolyte resistance and good bonding performance with the positive electrode sheet 102 and / or the negative electrode sheet 101. When the positive electrode sheet 102 and / or the negative electrode sheet 101 is subjected to pressure, the adhesive paper 106 plays a buffering role, which can greatly improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.

[0129] In some embodiments of the present application, the adhesive layer of the adhesive tape 106 is attached to at least one side of the positive electrode plate 102 and is in contact with the positive electrode plate 102. The hot melt adhesive of the adhesive layer has good electrolyte resistance and good bonding performance with the electrode plate. When the electrode plate is subjected to pressure, the hot melt adhesive acts as a buffer, which can greatly improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.

[0130] In some embodiments of the present application, reference Figure 1 and Figure 2 , Figure 2 It is part of the positive electrode sheet. The positive electrode sheet 102 includes alternating flat sections 102-2 and bent sections 102-1. Correspondingly, the negative electrode sheet 101 also has a flat section and a bent section 101-1. The adhesive tape 106 is provided on at least one side of the bent section 102-1 of the positive electrode sheet. As a result, the bent section 102-1 of the positive electrode sheet has an arc-shaped area and is subjected to high forces. Providing adhesive tape 106 on at least one side of the bent section 102-1 of the positive electrode sheet can effectively alleviate the problem of electrode sheet cracking, extend the life of the battery cell, and not affect the normal operation of the battery cell.

[0131] In some embodiments of the present application, the adhesive tape 106 is provided on at least one side of the bent section 102-1 of the positive electrode tab near the center of the wound battery cell 10. Thus, the bent section 102-1 of the positive electrode tab near the center of the wound battery cell 10 is subjected to high stress and is prone to cracking. Providing the adhesive tape 106 on at least one side of the bend 104 of the positive electrode tab near the center of the wound battery cell 10 can alleviate the problem of tab cracking and increase the life of the battery cell. Furthermore, the adhesive tape is precisely provided at the location where the tab is prone to cracking, eliminating excess adhesive tape. Furthermore, the wound battery cell has low resistance to active ion shuttling and high energy density.

[0132] It can be understood that the “bent section of the positive electrode sheet close to the center of the wound battery cell” refers to the innermost circle of the positive electrode sheet of the wound battery cell.

[0133] In some embodiments of the present application, the adhesive tape 106 is provided on both sides of the bent section 102-1 of the positive electrode sheet near the center of the wound battery cell 10. In this way, the adhesive tape 106 relieves pressure from both sides, which can greatly improve the problem of sheet cracking and increase the life of the battery cell.

[0134] In some embodiments of the present application, the positive electrode plate includes a positive electrode current collector, which can be a metal foil, a metal foam or a composite current collector. For example, as the metal foil, aluminum or stainless steel with a silver surface treatment, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, nickel or titanium, etc. can be used. The composite current collector may include a polymer material base and a metal layer. The foam metal may be nickel foam, copper foam, aluminum foam, alloy foam, or carbon foam, etc. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0135] In some embodiments of the present application, the positive electrode plate may further include a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material. The specific type of the positive electrode active material is not limited, and active materials known in the art that can be used for battery positive electrodes can be used. Those skilled in the art can select according to actual needs.

[0136] As an example, the positive electrode active material may include, but is not limited to, at least one of a lithium transition metal oxide, an olivine-structured lithium-containing phosphate, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their modified compounds. These materials can all be obtained through commercial channels.

[0137] For example, when the battery is a sodium ion battery, as an example, the positive electrode active material may include, but is not limited to, at least one of a layered transition metal oxide, a polyanion compound, and a Prussian blue analog.

[0138] Examples of the layered transition metal oxides include:

[0139] Na 1-x Cu h Fe k Mn l M 1 m O 2-y , where M 1is at least one of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn and Ba, 0 <x≤0.33,0<h≤0.24,0≤k≤0.32,0<l≤0.68,0≤m<0.1,h+k+l+m=1,0≤y<0.2;

[0140] Na 0.67 Mn 0.7 Ni z M 2 0.3-z O2, where M 2 is at least one of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn and Ba, 0 <z≤0.1;

[0141] Na a Li b Ni c Mn d Fe e O2, of which 0.67 <a≤1,0<b<0.2,0<c<0.3,0.67<d+e<0.8,b+c+d+e=1。

[0142] Examples of the polyanionic compound include:

[0143] A 1 f M 3 g (PO4) i O j X 1 3-j , where A 1 is at least one of H, Li, Na, K and NH4, M 3 is at least one of Ti, Cr, Mn, Fe, Co, Ni, V, Cu and Zn, X 1 is at least one of F, Cl and Br, 0 <f≤4,0<g≤2,1≤i≤3,0≤j≤2;

[0144] Na n M 4 PO4X 2 , where M 4 is at least one of Mn, Fe, Co, Ni, Cu and Zn, X 2 is at least one of F, Cl and Br, 0 <n≤2;

[0145] Na p M 5 q (SO4)3, where M 5is at least one of Mn, Fe, Co, Ni, Cu, and Zn, 0 < p ≤ 2, 0 < q ≤ 2;

[0146] Na s Mn t Fe 3-t (PO4)2(P2O7), where 0 < s ≤ 4, 0 ≤ t ≤ 3, for example, t is 0, 1, 1.5, 2, or 3.

[0147] As an example of the above Prussian blue analogues, for example, the following can be listed:

[0148] A u M 6 v [M 7 (CN)6] w ·xH2O, where A is H + 、NH4 + 、at least one of alkali metal cations and alkaline earth metal cations, M 6 and M 7 are each independently at least one of transition metal cations, 0 < u ≤ 2, 0 < v ≤ 1, 0 < w ≤ 1, 0 < x < 6. For example, A is H + 、Li + 、Na + 、K + 、NH4 + 、Rb + 、Cs + 、Fr + 、Be 2+ 、Mg 2+ 、Ca 2+ 、Sr 2+ 、Ba 2+ and Ra 2+ at least one of, M 6 and M 7 are each independently cations of at least one transition metal element of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn, and W.

[0149] The modified compounds of the above materials can be doping modification and / or surface coating modification of the materials.

[0150] The positive electrode active material layer usually also optionally includes a binder, a conductive agent, and other optional additives.

[0151] As an example, the conductive agent can include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, SuperP (SP), graphene, and carbon nanofibers.

[0152] As an example, the adhesive may include at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0153] In some embodiments of the present application, the negative electrode plate includes a negative electrode current collector, which can be a metal foil, a metal foam, or a composite current collector. For example, as the metal foil, aluminum or stainless steel with a silver surface treatment, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, nickel, or titanium can be used. The foam metal can be nickel foam, copper foam, aluminum foam, alloy foam, or carbon foam. The composite current collector can include a polymer material base layer and a metal layer. The composite current collector can be formed by disposing a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0154] In some embodiments of the present application, the negative electrode plate may further include a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material. The specific type of the negative electrode active material is not limited, and active materials known in the art that can be used for battery negative electrodes can be used. Those skilled in the art can select according to actual needs.

[0155] As an example, the negative electrode active material may include, but is not limited to, at least one of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-based materials, and tin-based materials. The silicon-based material may include at least one of elemental silicon, silicon oxides (e.g., silicon monoxide), silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxides, and tin alloys. These materials can all be obtained commercially.

[0156] In some embodiments of the present application, in order to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.

[0157] The negative electrode active material layer may also optionally include a binder, a conductive agent, and other optional auxiliary agents.

[0158] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0159] As an example, the adhesive may include at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB).

[0160] As examples, other optional additives may include thickeners and dispersants (eg, sodium carboxymethyl cellulose CMC-Na), and PTC thermistor materials.

[0161] In some embodiments of the present application, as the above-mentioned isolation membrane, the present application has no special restrictions, and any well-known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can be a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.

[0162] In some embodiments of the present application, the wound battery cell may further include an electrolyte, which may include an electrolyte salt and a solvent.

[0163] As an example, when the battery is a lithium-ion battery, the electrolyte lithium salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0164] As an example, when the battery is a sodium ion battery, the electrolyte sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethanesulfonate, and sodium bis(trifluoromethylsulfonyl)imide.

[0165] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0166] In some embodiments of the present application, the electrolyte further includes additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives capable of improving certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature performance.

[0167] The embodiment of the present application has no particular limitation on the shape of the battery, which can be cylindrical, square or any other shape. Figure 3 The secondary battery 1 is a square structure as an example.

[0168] The fifth aspect of the present application provides a battery comprising the wound battery cell according to the fourth aspect of the present application, thereby providing the battery with a longer lifespan.

[0169] Typically, a battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The separator is placed between the positive and negative electrodes to isolate them. The electrolyte conducts ions between the positive and negative electrodes.

[0170] In some embodiments of the present application, the battery 1 may include an outer packaging for packaging the positive electrode sheet, the negative electrode sheet, and the electrolyte.

[0171] In some embodiments of the present application, the outer packaging may include a housing and a cover. The housing may include a bottom plate and side plates connected to the bottom plate, with the bottom plate and side plates enclosing a receiving cavity. The housing may have an opening communicating with the receiving cavity, and the cover may be positioned over the opening to seal the receiving cavity.

[0172] The positive electrode sheet, negative electrode sheet, and separator can be wound or laminated to form an electrode assembly. The electrode assembly is encapsulated in the housing. The electrolyte is infiltrated into the electrode assembly. The number of electrode assemblies in a battery can be one or more, and can be adjusted according to needs.

[0173] In some embodiments of the present application, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0174] The outer packaging of the battery may also be a soft bag, such as a bag-type soft bag. The material of the soft bag may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0175] In some embodiments of the present application, batteries can be assembled into a battery module. The battery module can contain multiple sodium ion batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0176] Figure 4 2 is an example of a battery module. Figure 4 In the battery module 2, the plurality of secondary batteries 1 may be arranged in sequence along the length of the battery module 2. Of course, they may also be arranged in any other manner. The plurality of secondary batteries 1 may further be fixed by fasteners.

[0177] The battery module 2 may further include a housing having a housing space, wherein the housing space accommodates a plurality of secondary batteries 1. In some embodiments of the present application, the battery modules may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0178] Figure 5 and 6 The battery pack 3 is used as an example. Figure 5 and 6 The battery pack 3 may include a battery box and multiple battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form an enclosed space for accommodating the battery modules 2. The multiple battery modules 2 can be arranged in the battery box in any manner.

[0179] A sixth aspect of the present application provides an electrical device comprising the battery according to the fifth aspect of the present application, thereby extending the life cycle of the electrical device.

[0180] As an example, the electrical device includes at least one of the battery, battery module, and battery pack. The battery, battery module, or battery pack can serve as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop computer), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck), an electric train, a ship, a satellite, or an energy storage system.

[0181] The electrical equipment may select the secondary battery 1 , the battery module 2 or the battery pack 3 according to its usage requirements.

[0182] Figure 7 This is an example of an electric device. This device includes a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module can be used.

[0183] As another example, electric devices may include mobile phones, tablet computers, and laptop computers. These electric devices are generally required to be lightweight and thin, and may use batteries as power sources.

[0184] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0185] Example 1

[0186] 1. Preparation of hot melt adhesive

[0187] The polyolefin, toughening resin, reinforcing resin and additives were mixed, first stirred at 1200 rpm for 60 minutes, then stirred at 800 rpm for 90 minutes to ensure that the components were evenly mixed, and finally filled and discharged to obtain a hot melt adhesive.

[0188] 2. Preparation of adhesive tape

[0189] Hot melt adhesive is coated on the polyethylene film to form an adhesive layer to obtain adhesive paper.

[0190] 3. Preparation of positive electrode sheet

[0191] The positive electrode active material LiNi 0.8 Co0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry, which is coated on the positive electrode collector aluminum foil. The positive electrode sheet is obtained through drying, cold pressing, slitting, and cutting processes, and adhesive tape is adhered to the bent section of the positive electrode sheet near the center of the wound battery cell.

[0192] 4. Preparation of negative electrode sheet

[0193] The negative electrode active material artificial graphite, conductive agent carbon black (Super P), binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) are mixed evenly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.

[0194] 5. The isolation film is made of polyethylene film.

[0195] 6. Preparation of electrolyte

[0196] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:70 to obtain an organic solvent, and fully dried electrolyte salt LiPF6 is dissolved in the organic solvent. The concentration of the electrolyte salt is 1.0 mol / L, and the mixture is evenly mixed to obtain an electrolyte solution.

[0197] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets to serve as an isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected into the dried battery. After vacuum packaging, standing, formation, and shaping processes, a secondary battery is obtained.

[0198] The hot melt adhesives of Examples 2-63 and Comparative Examples 1-4 are the same as those of Example 1 except for the different parameters (see Table 1).

[0199] Table 1

[0200]

[0201]

[0202]

[0203]

[0204]

[0205]

[0206] The positive electrode sheet coated with hot melt adhesive was immersed in the above electrolyte. The bonding strength between the hot melt adhesive and the current collector was tested before immersion, after immersion for 1 day, 4 days, and 7 days. The dissolution rate and swelling rate of the hot melt adhesive in the electrolyte were also measured. The test results are shown in Table 2. The test method is as follows:

[0207] 1. Adhesion test before immersion:

[0208] Cut the sample into a size of 20×100mm for later use; take a stainless steel plate with a clean surface, wipe both sides of the plate with alcohol, then stick the cut sample horizontally on the surface of the stainless steel plate, and roll it horizontally with a 2kg roller for 2 circles to make the adhesive tape and the steel plate fit tightly; bend one end of the sample in the opposite direction with a bending angle of 180°; use a high-speed rail tensile testing machine to test, fix one end of the stainless steel to the lower fixture of the tensile testing machine, and fix the bent end of the sample to the upper fixture, adjust the angle of the sample to ensure that the upper and lower ends are in a vertical position, and then stretch the sample at a speed of 50mm / min until the sample is completely peeled off from the substrate, and record the displacement and force during the process. It is generally believed that the force when the force is balanced is the adhesion of the sample.

[0209] 2. Adhesion test after soaking in electrolyte:

[0210] Cut the sample into 20×100mm size for later use; take a stainless steel plate with a clean surface, wipe both sides of the plate with alcohol, then stick the cut sample horizontally on the surface of the stainless steel plate, and roll it horizontally with a 2kg roller for 2 circles to make the adhesive tape and the steel plate fit tightly; put the sample into an aluminum box filled with electrolyte, seal it with tin foil, and put it into a forced air drying oven with a set temperature of 70℃. Take out the sample after soaking for 1 day, 4 days and 7 days respectively, wipe off the electrolyte on the surface of the adhesive with dust-free paper, let it stand in the air for 10 minutes, and then start the adhesion test. The method is the same as the adhesion test before soaking in 1.

[0211] 3. Swelling rate test:

[0212] Film preparation: Take a certain amount of prepared hot melt adhesive and place it in a blast drying oven, set it at 70℃ and dry it for 24 hours to completely evaporate the solvent and make a film with a solid content of 100%;

[0213] 1) Weigh a certain mass of film, record it as M3

[0214] 2) Immerse in electrolyte at 70°C for 5 hours;

[0215] 3) Take out the hot melt adhesive and wipe the surface dry with dust-free paper;

[0216] 4) After standing for 20 minutes, weigh it and record it as M4

[0217] 5) Calculate the swelling ratio = (M4-M3) x 100% / M3.

[0218] 4. Dissolution rate test:

[0219] 1) Weigh a certain mass of film, record it as M1

[0220] 2) Immerse in electrolyte at 70°C for 5 hours;

[0221] 3) Take out the membrane and wipe the solvent off the surface of the membrane with dust-free paper;

[0222] 4) Place the film in an oven at 90°C and dry for 24 hours;

[0223] 5) Take out the membrane and wipe the solvent on the surface of the membrane with dust-free paper

[0224] 6) Place the film in an oven at 90°C and dry for 24 hours.

[0225] 7) Take out the membrane and weigh it, record it as M2

[0226] 8) Calculate the dissolution rate = (M1-M2) × 100% / M1

[0227] Table 2

[0228]

[0229]

[0230]

[0231] As shown in Table 2, the three components of the hot melt adhesives in Examples 1-63 of the present application work together to achieve a low dissolution rate in the electrolyte, minimal change in adhesion after immersion in the electrolyte, and excellent electrolyte resistance. The hot melt adhesive swells after immersion in the electrolyte, increasing the spacing between the hot melt adhesive chains and allowing active ions to freely shuttle between them. This means that the hot melt adhesive does not affect the normal operation of the wound battery cell and can act as a buffer, mitigating electrode cracking.

[0232] The solubility parameter of the polyolefin in Comparative Example 1 is not within the range of the embodiments of the present application, Comparative Examples 2 and 3 lack a component, and Comparative Example 4 uses commercially available hot melt adhesive, and its electrolyte resistance and adhesion are far lower than those of the embodiments of the present application.

[0233] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A hot melt adhesive, characterized in that: include: Polyolefin, toughening resin and reinforcing resin, wherein the solubility parameter of the polyolefin is 15 cal 1 / 2 / cm 3 / 2 -19cal 1 / 2 / cm 3 / 2 .

2. The hot melt adhesive according to claim 1, characterized in that: The dissolution rate of the hot melt adhesive in the organic solvent is less than or equal to 10%, and can be optionally 1%-6%.

3. The hot melt adhesive according to claim 1 or 2, characterized in that: The hot melt adhesive comprises 5-50 parts by weight of polyolefin, 10-40 parts by weight of toughening resin and 10-40 parts by weight of reinforcing resin. Optionally, the hot melt adhesive comprises 20-30 parts by weight of polyolefin, 15-25 parts by weight of toughening resin and 20-30 parts by weight of reinforcing resin.

4. The hot melt adhesive according to any one of claims 1 to 3, characterized in that: The solubility parameter of the polyolefin is 15 cal 1 / 2 / cm 3 / 2 -18cal 1 / 2 / cm 3 / 2 , optional 16cal 1 / 2 / cm 3 / 2 -17cal 1 / 2 / cm 3 / 2 .

5. The hot melt adhesive according to any one of claims 1 to 4, characterized in that: The weight average molecular weight of the polyolefin is 20,000-100,000, and can be optionally 30,000-50,000.

6. The hot melt adhesive according to any one of claims 1 to 5, characterized in that: The melting point of the polyolefin is 130°C-150°C, and can be optionally 140°C-150°C.

7. The hot melt adhesive according to any one of claims 1 to 6, characterized in that: The crystallinity of the polyolefin is 40%-60%, and optionally 40%-50%.

8. The hot melt adhesive according to any one of claims 1 to 7, characterized in that: The polyolefin includes at least one of polypropylene, polyethylene and polystyrene.

9. The hot melt adhesive according to any one of claims 1 to 8, characterized in that: The weight average molecular weight of the toughening resin is 10,000-100,000, and can be optionally 30,000-60,000.

10. The hot melt adhesive according to any one of claims 1 to 9, characterized in that: The branching degree of the toughening resin is 100-500, and can be optionally 100-200.

11. The hot melt adhesive according to any one of claims 1 to 10, characterized in that: The toughening resin includes at least one of polybutyl acrylate, polyisooctyl acrylate, amino-terminated liquid nitrile rubber and vinyl-terminated liquid nitrile rubber.

12. The hot melt adhesive according to any one of claims 1 to 11, characterized in that: The weight average molecular weight of the reinforcing resin is 30,000-100,000, and can be optionally 50,000-80,000.

13. The hot melt adhesive according to any one of claims 1 to 12, characterized in that: The branching degree of the reinforced resin is 100-500, and can be optionally 100-200.

14. The hot melt adhesive according to any one of claims 1 to 13, characterized in that: The reinforcing resin includes at least one of butyl rubber and styrene butadiene rubber.

15. The hot melt adhesive according to any one of claims 1 to 14, characterized in that: The hot melt adhesive further comprises 5 to 30 parts by weight of a tackifying resin, and optionally, further comprises 10 to 20 parts by weight of a tackifying resin.

16. The hot melt adhesive according to claim 15, characterized in that: The weight average molecular weight of the tackifying resin is 1000-10000, and can be optionally 3000-5000.

17. The hot melt adhesive according to claim 15 or 16, characterized in that: The melting point of the tackifying resin is 60°C-90°C, and can be optionally 75°C-85°C.

18. The hot melt adhesive according to any one of claims 15 to 17, characterized in that: The viscosity of the tackifying resin at 100° C. is 200 mPa·S-1500 mPa·S, and can be optionally 500 mPa·S-1000 mPa·S.

19. The hot melt adhesive according to any one of claims 15 to 18, characterized in that: The tackifying resin includes at least one of C5 / C9 copolymerized petroleum resin, hydrogenated petroleum resin and terpene resin.

20. The hot melt adhesive according to any one of claims 1 to 19, characterized in that: The hot melt adhesive further comprises 0.1 to 1 parts by weight of an additive. Optionally, the hot melt adhesive further comprises 0.1 to 0.5 parts by weight of an additive.

21. The hot melt adhesive according to claim 20, characterized in that: The additive includes at least one of N-phenyl-β-naphthylamine, 2,6-di-tert-butyl-p-cresol, 3-methyl-6-tert-butylphenol and pentaerythritol tetrakis (3-laurylthiopropionate).

22. A method for preparing the hot melt adhesive according to any one of claims 1 to 21, characterized in that: include: The polyolefin, toughening resin and reinforcing resin are mixed to obtain a hot melt adhesive, wherein the solubility parameter of the polyolefin is 15 cal 1 / 2 / cm 3 / 2 -19cal 1 / 2 / cm 3 / 2 .

23. A tape, characterized in that: It comprises a substrate and an adhesive layer arranged on at least one side of the substrate, wherein the adhesive layer comprises the hot melt adhesive described in any one of claims 1 to 21 or the hot melt adhesive prepared by the method described in claim 22.

24. The adhesive tape according to claim 23, characterized in that: The adhesive tape meets at least one of the following conditions: The thickness ratio of the adhesive layer to the substrate is (1-4):10, and can be (1-2):10; The thickness of the adhesive tape is 2 μm-8 μm, and can be optionally 2 μm-4 μm.

25. A wound battery cell, characterized in that: It comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked and wound in sequence, and the adhesive tape according to claim 23 or 24 is provided between the positive electrode sheet and the separator and / or between the negative electrode sheet and the separator.

26. The wound battery cell according to claim 25, characterized in that: The positive electrode plate comprises planar sections and bent sections which are arranged alternately, and the adhesive tape is disposed on at least one side of the bent section.

27. The wound battery cell according to claim 26, characterized in that: The adhesive tape is arranged on at least one side of the bending section close to the center of the wound battery core.

28. A battery, characterized in that: A wound battery cell comprising any one of claims 25-27.

29. An electrical equipment, characterized in that: Comprising the battery of claim 28.

Citation Information

Patent Citations

  • Hot melt adhesive and application thereof

    CN110511703A

  • Hot melt adhesive, preparation method thereof, secondary battery, battery module, battery pack and electric device

    CN115838575A

  • Hot melt adhesive film and flow battery stack sealing method applying same

    CN115948131A

  • Binder composition, electrochemical device, and electric device

    CN115975550A

  • Hot-melt adhesive composition, producing method for electrode laminate, and secondary battery including electrode laminate

    JP2019210369A